Revolusi Islam, Gerakan Islam dan Negara Islam: Studi Atas Pemikiran Politik Kalim Siddiqui - Mulyani (Budapest International Research and Critics University, 2016)
According to Siddiqui, Islamic movement is a tradional instru- ment for change. Islamic movement is not a political movement with a manifesto written by a committee. It also not an ideology conceptualized by philosophers, historians, activists, and thinkers from various faculties. The Islamic movement is purely the manifestation of God. So it will get His direct keep and maintenance. Starting from the movement led by the Prophet (PBUH), the corrective agents spread widely in Islamic history, like a labirint planted in political culture of Muslims.